Hemolytic disease of fetus and newborn due to maternal AlloAnti-S antibody - Suresh Kumar Iyyapan; Hari Haran Annadurai; Gokhula Prasath Thangavel; Hemamalini Natesan (Asian Journal of Transfusion Science)
Hemolytic disease of foetus and newborn (HDFN) is a disease characterized by the destruction of fetal red cells by the maternal antibodies which occurs due to allo immunization in the mother by feto-maternal blood group incompatibility.The antibodies most frequently implicated in HDFN may vary depending on the demographic location under consideration. In areas where RhIg administration is available, ABO antibodies are more commonly implicated. Following ABO antibodies, anti-RhD antibodies which are of IgG type are more commonly implicated in causing HDFN. HDFN caused by other Rh system antibodies namely anti-C, anti-c, anti-E, anti- e, MNS, KEL, FY, JK, and DI systems is less frequent. We have reported one such rare case of Hemolytic disease of fetus and newborn due to Anti--S. During the routine antenatal screening for irregular antibodies, using antibody identification cell panel BIO-RAD (ID Diapanel 11x4) which belongs to lot number (06171.47.x – 06271.47.x), anti-S was identified in the mother serum. The baby was non-hydropic at birth with an increase in bilirubin which required high-intensity phototherapy.